2004
DOI: 10.1677/joe.0.1810429
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of urinary sorbitol excretion in WBN-kob diabetic rats - treatment with an aldose reductase inhibitor

Abstract: An accerelated polyol pathway in diabetes contributes to the development of diabetic complications. To elucidate diabetic nephropathy involving also renal tubular damage, we measured urinary sorbitol concentration concomitantly with urinary N-acetyl--glucosaminidase (NAG) excretion in WBN-kob diabetic rats.Twenty-four-hour urinary sorbitol concentrations increased in the diabetic rats in parallel with whole blood sorbitol concentrations. An increase in 24-h urinary NAG excretion coincided with the elevated ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Bendazac lysine (BDL) was provided by Supereyes Pharmaceutical (Pinghu, China) and suspended in 1% carboxymethyl cellulose (CMC) at different concentrations (1.0, 2.0 and 4.0%). Epalrestat (EPS) was kindly donated by Yangtze River Pharmaceutical Group (Taizhou, China) and served as a positive control drug suspended in 1% CMC 14,15 . Streptozotocin was purchased from Biomol Research Laboratory (Plymouth Meeting, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Bendazac lysine (BDL) was provided by Supereyes Pharmaceutical (Pinghu, China) and suspended in 1% carboxymethyl cellulose (CMC) at different concentrations (1.0, 2.0 and 4.0%). Epalrestat (EPS) was kindly donated by Yangtze River Pharmaceutical Group (Taizhou, China) and served as a positive control drug suspended in 1% CMC 14,15 . Streptozotocin was purchased from Biomol Research Laboratory (Plymouth Meeting, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…As AR is the ratecontrolling enzyme in the polyol pathway, epalrestat can significantly inhibit AR and downregulate polyol metabolites (such as sorbitol and fructose) to alleviate osmotic stress [1]. Except for diabetes neuropathy, recent accumulative evidence has suggested the potential application of ARIs for renal protection in DN [12,13]. Li et al [14] observed significant depletion of myoinositol in the renal cortex of diabetic kidneys in db/db mice, which is observed in other animal models [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The level of metabolites excreted reects both the adequacy of the diet and the degree of body health, especially for 2-oxoglutarate, 61 although there is no direct evidence to link the declined excretion of these metabolites with health. According to previous studies, the increased excretion of 2-oxoglutarate, sorbitol and glucose are related to metabolism-associated diseases like diabetes, 61,62 interstitial cystitis/painful bladder syndrome, 63 gastric cancer, 64 and polycystic kidney disease. 65 Moreover, Ekblond et al 66 have proposed that the declined levels of urinary glucose excretion might serve as an evaluation factor for health protection.…”
Section: Discussionmentioning
confidence: 98%